Comparative Studies of Water and Sediment Qualities of Some Dams in Kwara State (Fountain Journal of Natural and Applied Sciences, 2016)
Potable water is becoming progressively scarce due to anthropogenic pollution and it has necessitated monitoring of water quality of rivers and dams as a subject of ongoing concern and research. This study was conducted to assess the quality of water collected from four different dams (Agba, Igbaja, Oloru and Omu-Aran) in Kwara State, Nigeria using standard procedures. Water and sediment samples were collected from three different spatial locations on the dams. The average values of most physicochemical parameters like pH, temperature, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Total Dissolved Solid (TDS), Total Hardness (TH), Alkalinity, some nutrients such as chloride (Cl-), sulphate (SO42-), phosphate (PO43-), nitrate (NO3-) and some heavy metals such as Cu, Zn have values that were within World Health Organisation (WHO) guidelines for drinking water for each of the dams while Cd and Fe concentrations were observed to be much higher than WHO guidelines for drinking water. This could be as a result of anthropogenic input. The dams’ sediments analyzed for heavy metals showed that Mn, Zn and Cd were high in the dams, which can be easily washed into the water body through leaching, thereby causing detrimental effect to the consumers.Keywords: geo-accumulation index, bioavailabilty, nutrient, dam, alkalinity.